PENGARUH MODEL PEMBELAJARAN BERPASANGAN DAN PERORANGAN TERHADAP HASIL PUKULAN LOB - Rini Puspita Sari; Herman Tarigan; Sudirman Husin (JUPE (Jurnal Penjaskesrek), 2013)
This study is aimed to find out the influence of doubles and singles model towards lob shot output on students of badminton extracurricular in SMA N 5 Bandar Lampung. The researcher applied comparative experiment as the approach in this study. There were 28 students of badminton extracurricular participated in this research; and because the number was less than 100 for population, so the 28 participants were supposed to be the sample. The participants were then devided into two groups; doubles model and singles model by using Ordinal Pairing. Clear Test was applied for the instrument with validity level 0.92 and reliability level 0.95. The data analysis was calculated with t-test. The result were concluded as folow: First, there was an influence of doubles model toward students' lob shot output; second, there was an influence of singles model towards students' lob shot output; third, there was a more significant influence of doubles model than singles model towards students' lob shot. The researcher concluded that both models gave influence on students' lob shot output, but the doubles one gave a more significant influence to improve students' lab shot output.Kata kunci: model pembelajaran berpasangan, model pembelajaran perorangan, pukulan lob.